SISTEM INFORMASI AKADEMIK MENGGUNAKAN KEAMANAN SECURE SOCKET LAYER DENGAN LOCAL SERVER HOSTING DAN SMS GATEWAY - Habib Hudaya (STEKOM PRESS, 2018)
PALAPA Semarang Vocational School is a school where the delivery of information by attachment to the bulletin board, so that in the delivery of information is felt to be less fast given the lack of means of communication between the school and students, parents and less optimal managing academic information. Academic Information System was developed using Secure Socket Layer (SSL) Security with Local Server Hosting and SMS Gateway and PHP as a programming language and using a MySQL database. Academic Information System is developed in the form of local server hosting and online security Secure Socket Layer (SSL) so that an effective and efficient job in supporting school activities will be achieved. With this SMS based information system it can be a solution. Keywords: Information Systems, Academic, SMS Gateway, Local Server Hosting, SSL, PHP. The essence of PALAPA Vocational School Semarang is a school where the delivery of information by attachment to the bulletin board, so that the delivery of information is felt to be less fast given the lack of means of communication between the school and students, parents and less optimal managing academic information. The Academic Information System was developed using Secure Socket Layer (SSL) Security with Local Server Hosting and SMS Gateway and PHP as a programming language and using a MySQL database. Academic Information System is developed in the form of local server hosting and online security Secure Socket Layer (SSL) so that an effective and efficient job will be achieved in supporting activities at school. With this SMS based information system it can be a solution.